Learning Evaluation Design Using Quizizz in Mathematics Subjects at Elementary School - Agustin, Sandra Aryani; Saputra, Hendra Nelva; Darman, Darman (research, training and philanthropy institution Natural Aceh, 2025)
This study aims to design a valid, reliable, and effective mathematics learning evaluation tool using Quizizz for grade VI students at SDN 1 Toronipa. The method used in this study is Research and Development (RnD) with a 4D development model. The validity test results showed that out of 25 questions tested, 15 were declared valid, while 10 other questions were invalid. The reliability test conducted using the Alpha Cronbach method produced a reliability coefficient of 0.960, indicating a very high level of Reliability. Analysis of the difficulty level of the questions revealed that 80% of the questions were in the